Rozwój technologii informacyjnych i komputerowych technologii jako czynnik mający wpływ na społeczne zdrowie osobowości = The de velopment of information and computer technology as the factor influencing social hea lth of the person - Ermolenko, Irina A.; Severin, Aleksei V. (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article analyzes various aspects of the impact of ICT on social and mental health of the individual. The psychological effects, phenomena and regularities that arise in Internet and computer environment. The emphasis on the ambivalent nature of cultural and psychological transformations in the field of development of higher mental functions of personality.
Keywords: społeczne zdrowie; dewiacja; uzależnienie od Internetu; komputerowa zależność; informacyjno-komputerowe technologie; wirtualna rzeczywistość; percepcyjne działania; adaptacja; postęp technologiczny; social health; deviancy; Internet addiction; computer addiction; computer information technology; cyberpsychology; virtual reality; perceptual actions; adaptation; technological progress